What Contributes to the Regularity of Patients with Hypertension or Diabetes Seeking Health Services? A Pilot Follow-Up, Observational Study in Two Sites in Hubei Province, China - Da, Feng (Switzerland, 2018)
Regular maintenance of non-communicable chronic diseases can constrain disease progression in diabetic and hypertensive patients. To identify the individual and social factors that are associated with positive health-seeking behaviors and regular maintenance of chronic diseases, we have conducted a follow up study in 2015 on diabetic and hypertensive patients in Hubei Province. We used binary logistic regression models to determine specific factors associated with diabetic and hypertensive patients that sought healthcare services for their conditions in accordance with current Chinese Centers for Disease Prevention and Control (CDC) guidelines. Our findings show that 42.16% of 510 people living with chronic conditions (PLCDs) sought health services in line with existing guidelines. Findings also show a higher probability (8.418 times) for PLCDs seeking healthcare services at higher-tiered hospitals (secondary and tertiary hospitals) than for PLCDs seeking care at primary hospitals (odds ratio (OR) = 8.418, 95% confidence interval (CI) = 4.82, 14.27, p < 0.001). These analyses underscore the importance of having patient advocates who can provide support, where necessary, and encourage positive health-seeking behavior. The study also shows a negative impact on regular maintenance for PLCDs in households with high financial constraints. In contrast, the study shows positive impacts for increased household income, age, and residency in rural locations. In sum, this study underscores the importance of primary hospitals as key points of care and critical players in care coordination for PLCDs. The study provides more evidence for Chinese policymakers seeking to contain costs and improve population health. The findings also underscore the need for community-based interventions, specifically interventions that link local primary hospitals, friends/family members, and PLCDs.